A gestão escolar no contexto das práticas e dos efeitos de uma política de formação de professores: PARFOR - Fernandez, Gisele Santos (2015)
The PARFOR (Plano Nacional de Formação de Professores da Educação Básica) is an emergencial initiative for basic education teachers of the public schools that was created to offer free courses of graduation in Pedagogia for teachers who work in the basic education, but didn´t have adequate graduation. This research focuses on two schools´ managers where 12 teachers work from one Education course refunded by Parfor. It´s intends to analyse schools manager´s conditions to support them so that they can consolidate declared gains for them in previous researches. For this, analyze official documents on managers and professionals of the school, in the federal and municipal scope and analyze the everyday routine of these professionals. Three main ideas guide this study: school as level meso of analysis, the paper of the actors in the implementation of policy and the school as place of students and teachers education. The research is supported in studies on the reception of politics in the bases of the systems of education, in this case, schools, (BOWE; BALL; GOLD, 1992; BALL, 1994; MAINARDES, 2006; MAINARDES; FERREIRA; TELLO, 2011), in this case, in schools, and on politics of teacher´s formation, especially, the Parfor (BRAZIL, 2009a, 2009b; GATTI, BARRETO, ANDRÉ, 2011; PESSOA, ARAÚJO, 2013). Concerning management´s approach, it call on Canário (2005), Sander (2007), Silva (2007), Dourado (2007), Vieira (2009), Paro (2012), Libâneo (2008), Luck (2009, 2012) and Lima (2011) and concerning school as a formation place, called on Canário (1998; 2005), Nóvoa (1999), Abdalla (2006) and Cunha (2008). It adopts qualitative approach with documentary analysis, schools observation, and interviews. The analysis of the data points to four main categories: policy as text, policy as discourse, pedagogical-formative management and structure and functioning of the school. Results indicate that managers have legal, personal, professional and material conditions to give pedagogical support to the teachers from Parfor education course; They set clear that the attendance vestige of the basic education in the kinder-garden level, still found in the discourses and the legal functional condition of the teachers act as hurdle for the purposes/intention of the analyzed policy. Finally, it reinforce that, despite of other conditions, each school receives and enact one policy according to its managers performance and leadership.